Sensor voltamétrico para detecção de trinitrotolueno baseado em nanocompósito de óxido de grafeno reduzido e nanotubos de carbono - Castro, Sílvia Vaz Fernandes de (2018)
2,4,6-trinitrotoluene (TNT) is an explosive compound widely used in terrorist attacks and military combats. Due to this use, it has become a growing concern in the areas of safety and environment. Thus, the present work presents for the first time the detection of TNT on reduced graphene oxide/multi-walled carbon nanotubes (rGO-MWCNT) nanocomposite. The thin film formation of this nanocomposite occurred at the cyclohexane/water immiscible interface of a mixture of MWCNT e rGO in the biphasic solution. The substrate for witch the film was transferred was a boron doped diamond (BDD) electrode and the square-wave voltammetry technique was used to determine TNT. Also films with only nanomaterials were prepared separately and all surfaces were evaluated for comparison purposes. The technique of Electrochemical Impedance Spectroscopy (EIS) used to characterize the obtained materials. This technique allowed the study of the modified surfaces, evidencing that the electron transfer processes for the redox probe are facilitated on surface modified with the nanocomposite. The sensor also showed improved analytical characteristics compared to the unmodified BDD and modified with precursors, such an increased sensitivity and accuracy in responses. The synergistic properties of both carbon nanomaterials on the film-modified surface resulted in a TNT sensor with a detection limit of 0.019 μmol L-1, wide linear range (0.5 – 1100 μmol L-1), with superior performance compared to other electrochemical sensor produced with carbon nanomaterials and reported in the literature. The interfacial method also presented a good reproducibility for different films obtained for the determination of TNT and a good stability when stored and used on different days. The nanocomposite film also provides selective response to TNT against some nitrocompounds such a cyclotrimethylenetrinitramine (RDX), pentaerythritol tetranitrate (PETN) and nitrobenzene. The results obtained demonstrate that the sensor presents as a great promise for the detection of other nitroaromatics as well as of other analytes.